The Relationship Between Local Knowledge and Community Participation in Bacukiki in the Implementation of Community-Based Tourism at Ladoma Agro - Faizah Layla Rohmah; Firman; Dwi Jarwanto (Prospect Publishing, 2025)
This study explores the relationship between local knowledge and community participation in the development of community-based ecotourism in Bacukiki, Parepare. At the heart of this initiative is the Ladoma Community Group, established as a local response to increasing environmental degradation and the need to integrate conservation efforts with sustainable tourism. The findings reveal that knowledge within the community is not solely derived from formal education systems, but also from everyday practices, traditional cultural values, and continuous social interactions among members. Despite variations in economic conditions and educational backgrounds, each member actively contributes ideas, resources, and actions that enable programs to run effectively and remain sustainable. The collaboration with PT Pertamina Patra Niaga FT Parepare further enhanced community capacity by providing training, introducing renewable energy technologies, and supporting agricultural innovation. The Ladoma experience demonstrates that inclusive and participatory approaches not only strengthen sustainability, but also build resilience and adaptability within local communities facing environmental challenges.